Knowledge Management and Acquisition for Intelligent Systems 12th Pacific Rim Knowledge Acquisition Workshop, PKAW 2012, Kuching, Malaysia, September 5-6, 2012, Proceedings - Richards, Deborah; Kang, Byeong Ho (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the proceedings of the 12th International Workshop on Knowledge Management and Acquisition for Intelligent Systems, PKAW 2012, held in Kuching, Malaysia, in September 2012. The 21 full papers and 11 short papers included in this volume were carefully reviewed and selected from 141 papers. They deal with knoweldge acquisition issues and evaluation; language, text and image processing; incremental knowledge acquisition; agent based knowledge acquisition and management; ontology-based approaches; WEB 2.0 methods and applications; and other applications.